FOREIGN EXPERIENCE IN DEVELOPING TYPES OF PERSONAL INSURANCE - Isaeva Xolbibi Boboqulovna (Modern American Journals, 2025)
This article analyzes best practices in developing personal insurance types in leading countries around the world. In particular, the institutional framework, regulatory mechanisms, and innovative approaches of personal insurance types such as life insurance, health insurance, and accident insurance in the United States, Germany, Japan, and other countries will be studied. It also provides suggestions on the possibilities of applying foreign experience in the conditions of Uzbekistan and solutions to existing problems.
Keywords: Personal insurance, international experience, life insurance, health insurance, industry innovations, institutional development.